EFFECTIVENESS OF USING ELEMENTS OF NANOTECHNOLOGY IN CONSTRUCTION MATERIALS SCIENCE (Spectrum Journal of Innovation, Reforms and Development, 2022)
Nanotechnology is an applied science that deals with the creation of fundamentally new instruments and materials at extremely small sizes, and studies the properties of various substances at the atomic and molecular level.